The Dutch UMTS-Auction - Eric van Damme (Center for Economic Studies and ifo Institute (CESifo), 2002)
In this paper I review the Dutch UMTS-auction that took place in the summer of 2000 and which, in contrast to the UK and German auctions, was generally considered to be a major flop. I analyse the policy process leading to the auction as well as the bidding behaviour in the auction, and provide an evaluation of both. I demonstrate that the case contains several useful lessons for other auction design problems.
Keywords: 330; auctions; telecommunications